European Dermatology Forum S1‐guideline on the diagnosis and treatment of sclerosing diseases of the skin, Part 1: localized scleroderma, systemic sclerosis and overlap syndromes. (9th August 2017) - Knobler, R.; Moinzadeh, P.; Hunzelmann, N.; Kreuter, A.; Cozzio, A.; Mouthon, L.; Cutolo, M.; Rongioletti, F.; Denton, C.P.; Rudnicka, L.; Frasin, L.A.; Smith, V.; et al.
Abstract: The term 'sclerosing diseases of the skin' comprises specific dermatological entities, which have fibrotic changes of the skin in common. These diseases mostly manifest in different clinical subtypes according to cutaneous and extracutaneous involvement and can sometimes be difficult to distinguish from each other. The present guideline focuses on characteristic clinical and histopathological features, diagnostic scores and the serum autoantibodies most useful for differential diagnosis. In addition, current strategies in the first‐ and advanced‐line therapy of sclerosing skin diseases are addressed in detail. Part 1 of this guideline provides clinicians with an overview of the diagnosis and treatment of localized scleroderma (morphea), and systemic sclerosis including overlap syndromes of systemic sclerosis with diseases of the rheumatological spectrum.